Pengembangan Konsep Bilateral Symmetry untuk Meningkatkan Kinerja Rantai Pasokan melalui Kualitas Sinergi pada Industri Komponen Otomotif di Indonesi - Purwani, Tri; Nurcholis, Lutfi (Jurnal Aplikasi Manajemen, 2015)
The specific aims of this study are: (1) Conducting an empirical testing and analyzingthe effects of: (a) the similarity of standardization ability and transparency on thequality of synergy, (b) the quality of synergies to the supply chain performance, (2) Providingthe information to the automakers and automotive parts about the importance of thesimilarity of standardization ability and transparency in common in order to improve thesupply chain performance, (3) Providing a practical contribution to the managerial andacademic circles in analyzing the similarity of standardization ability and transparencythat could improve supply chain performance. The population of the study was the entireautomotive component industries in Indonesia, including 189 companies (Data GAIKINDO,AISI and GIAMM). This subject of the study consists of managers or staffs authorized by thedirectors. The sampling method uses purposive sampling. This study has a target 105 respondentsto comply with the AMOS program. The population target including automotive componentcompany located in Jakarta, Bekasi, Karawang, Bogor, Surabaya, and Semarang.Data were collected from the questionnaires in which processed through descriptive statistics,inferential statistics and testing SEM. This study generates a new concept of BilateralSymmetry that can be developed for further research.